(untitled) (Fiep Bulletin - online, 2011)
This is a descriptive study, a quantitative and non-participant observation conducted at Hospital Universitário Onofre Lopes (HUOL). Aimed to verify the relationship between knowledge and practice the technique of hand washing by the nursing team in the ICU of a university hospital. The population was composed of 41 professionals of the nursing team that works in the ICU. The project was submitted to the ethics committee on research getting assent (No. 278/09). The results were tabulated in Excel and analyzed using descriptive and inferential statistics through SPSS version 15.0. During the monitoring and observation of all procedures of the professional nursing team in an ICU found a predominance of professional of IEL and FUNPEC - (64.3%), female (p = 0.654), aged 21 to 35 years (p = 0.055), with average level of education (p = 0.001). Of these, 11.6% were nurses and 88.4% nursing technicians. We emphasize the importance of what was found in knowledge and practice in the implementation of hand washing, most professionals regard it should be performed before and after every procedure (81.4%), but in practice we have seen conflicting data, where 40.3% of the professionals do it properly. In the category of technical nursing, to conduct more frequent was inadequate hand washing (56%), as well as among professional nurses (57.1%).